The Influence of User Experience and E-Service Quality on Customer Loyalty Through Customer Satisfaction Mediation (Study on Mobile Coffee Shop Applications in Indonesia) - Syahreza Prakasa Nasution; Karto Adiwijaya (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Purpose-This study aims to examine the influence of user experience and e-service quality on customer loyalty with customer satisfaction as a mediator in mobile coffee shop applications in Indonesia.Design/methodology/approach -This research is a quantitative research which uses a survey methodology with SEM-PLS analysis. This study involved 270 respondents who are active users of various mobile coffee shop applications.Findings-The results indicated that user experience significantly affects e-service quality and directly impacts customer satisfaction. Although e-service quality did not show a positive effect on customer loyalty, the study found no significant evidence that e-service quality directly impacts customer satisfaction. However, customer satisfaction significantly mediates the relationship between user experience and customer loyalty. Additionally, age serves as a moderating variable in the relationship between customer satisfaction and customer loyalty. These findings underscore the importance of enhancing user experience and suggest that improving electronic service quality may not be sufficient without directly increasing customer satisfaction to build customer loyalty.Originality/value-This study used age as a moderating variable, and combined it with UX and customer satisfaction model.